Meneguhkan Pancasila Sebagai Ideologi Bernegara - Muhammad Chairul Huda (Resolusi: Jurnal Sosial Politik, 2018)
Pancasila as the basis of the state of Indonesia has the values of the balance of law, namely the value of divinity, human values, and value. By understanding Pancasila through historical understanding, this paper concludes that Pancasila becomes a universal and comprehensive state ideology that contains hablumminallah, hablumminannas, and hablum minal alam to reach the goal of rahmatan lil alamin. As a foundation of philosophy, Pancasila obtains a source of value in the context of the dynamic journey of cultural history of the nation. The establishment of the source of value embodied in the national philosophy system has been going on in a long history. The existence of Pancasila in law is a milestone of achievement in a circle of the state of law. Conversely, the absence of Pancasila will give birth to legal problems and the creation of unstructured legal construction.